Mass Spectrometry (MS) Profiling on Potent Anticancer Fractions of Calthropella sp. - Susilowati, Fitria (University Of Darussalam Gontor, 2022)
A research on isolation and in vitro cytotoxic assay of active fractions of marine sponge Calthropella sp. from Krakal Beach Gunungkidul had been carried out. This study aims to analyze the Mass Spectrometry (MS) profile of potent anticancer fractions of marine sponge Calthropella sp. The two potent fractions (F1 and F2) were analyzed by High Resolution Liquid Chromatography-Mass Spectrometry (HR LC-MS) to identify the compounds exist in each fractions. The LC-MS analyses were conducted on the best elution system, isocratic elution of 80% MeCN (with 0.1% formic acid) + 20% milliQ H2O (with 0.1% formic acid). Based on LC-MS analyses, it is strongly predicted that F1 consist of 4'-N-methyl-5'- hydroxystaurosporine, 24-methyleneergost-4-ene-3-one, and one new compound. F2 is predicted to consist bengamide Q, clavepictine A, 4'-N-methyl-5’-hydroxystaurosporine, biemnic acid, carteriofenone A, and one new compound